Karakter Populasi Wereng Hijau, Nephotettix virescens (Hemiptera: Cicadellidae) di Wilayah Endemi dan Non Endemi Penyakit Tungro Padi - Supriyadi Supriyadi; Kasumbogo Untung; Andi Trisyono; Triwibowo Yuwono (Universitas Gadjah Mada, 2004)
The objectives of this research were to determine the species composition, distribution pattern and virus transmission properties of N. virescens. Sweep net sampling of the leafhopper and others tungro vectors population were conducted from endemic areas in Central Java, East Java and Bali and also non endemic areas from Central Java and East Java. The species composition and distribution pattern of the leafhopper were studied in seedbeds and early stage of rice crop (30 days after transplanting). Inoculation test using Cisadane seedlings was conducted to determine the efficiency of virus transmission by N. virescens colonies. Four tungro virus vectors were found in all areas, namely N. virescens, N. nigropictus, N. malayanus, and Recilia sp. The domination of N. virescens occurred either in the endemic area or the non endemic areas. However, the domination of N. virescens did not correlate with the occurrence of the disease in the endemic area. The distribution pattern of N. virescens was regular. The number of N. virescens active transmitter in the endemic area was higher than that in the non-endemic areas. In addition, the female of N. virescens was more efficient in transmitting the tungro virus than that of the male.